2020
DOI: 10.3390/ijms21010329
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Analysis Supports a Causal Relationship between Maternal Hyperglycemia and Placental DNA Methylation Variations at the Leptin Gene Locus and Cord Blood Leptin Levels

Abstract: Changes in fetal DNA methylation (DNAm) of the leptin (LEP) gene have been associated with exposure to maternal hyperglycemia, but their links with childhood obesity risk are still unclear. We investigated the association between maternal hyperglycemia, placental LEP DNAm (25 5′-C-phosphate-G-3′ (CpG) sites), neonatal leptinemia, and adiposity (i.e., BMI and skinfold thickness (ST) (subscapular (SS) + triceps (TR) skinfold measures, and the ratio of SS:TR) at 3-years-old, in 259 mother–child dyads, from Gen3G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
3
17
1
Order By: Relevance
“…Our findings also showed that higher post‐load maternal glucose level, and not fasting glucose, in the second trimester was associated with greater total body fat percentage in children using DXA at 5 years of age. These findings are in line with some studies evaluating adiposity in 5 to 7 years' old children 5‐7 but not all studies are consistent with these observations 9,14‐16 . Previous studies that showed associations between 1 and 2 hours post‐OGTT glucose levels and childhood adiposity have reported findings using indirect adiposity measures such as BMI z ‐score 5 or sum of skinfolds in children exposed to GDM 6 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our findings also showed that higher post‐load maternal glucose level, and not fasting glucose, in the second trimester was associated with greater total body fat percentage in children using DXA at 5 years of age. These findings are in line with some studies evaluating adiposity in 5 to 7 years' old children 5‐7 but not all studies are consistent with these observations 9,14‐16 . Previous studies that showed associations between 1 and 2 hours post‐OGTT glucose levels and childhood adiposity have reported findings using indirect adiposity measures such as BMI z ‐score 5 or sum of skinfolds in children exposed to GDM 6 .…”
Section: Discussionsupporting
confidence: 87%
“…The development of adipose tissue starts at 14 to 16 weeks of gestation, 31 and if relative hyperglycaemia was already present early in pregnancy, development of the pre‐adipocytes and the adipocytes in mid‐pregnancy might be impacted. In previous reports from our group, 15,18 Mendelian Randomization and mediation analyses supported causal relationship between maternal glucose in pregnancy and DNA methylation of leptin gene ( LEP ) in placenta and in cord‐blood samples. In line with this hypothesis, in a case‐control of young adults (26‐35 years‐old), pre‐adipocytes isolated from subcutaneous adipose tissue (SAT) biopsy and cultured in vitro showed a decrease in LEP methylation (in differentiation study), plus an increase in leptin secretion and expression in the GDM‐exposed or the T1D‐exposed compared to the control group 32 .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations